﻿Animal disease report Antilles Zones. Bluetongue studies in the Caribbean - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The volumen 3 is divided into several numbers